(untitled) - McMahon, April (Great Britain, 2002)
A clear and accessible introductory text on the phonological structure of the English language, English phonology is an ideal text for those with no prior knowledge of the subject. This market-leading textbook teaches undergraduate students and non-native English speakers the fundamentals of articulatory phonetics and phonology in an engaging, easy-to-understand style.
Âm vị học Tiếng Anh
Keywords: Tiếng Anh,English language; Âm vị học,Phonology